The Bacterial Elicitor Flagellin Activates Its Receptor in Tomato Cells According to the Address–Message Concept - Meindl, Thomas (American Society of Plant Physiologists, 2000)
flg22, a peptide corresponding to the most conserved domain of bacterial flagellin, acts as a potent elicitor in plants. Here, we have used an iodinated derivative of flg22 ((125)I-labeled Tyr-flg22) as a molecular probe for the flagellin receptor in tomato cells. This radioligand showed rapid binding to a single class of specific, saturable, high-affinity receptor sites in intact cells and membrane preparations. Binding, although essentially nonreversible under physiological conditions, was not covalent, and chemical cross-linking was required to specifically label a single polypeptide of 115 kD. Intact flagellin and elicitor-active flagellin peptides but not biologically inactive analogs efficiently competed for binding of radioligand. Peptides lacking the C terminus of the conserved domain, previously found to act as competitive antagonists of elicitor action in tomato cells, also competed for binding of radioligand. Thus, this novel, high-affinity binding site exhibited all the characteristics expected of a functional receptor of bacterial flagellin. For a model of receptor activation, we propose a two-step mechanism according to the address–message concept, in which binding of the N terminus (address) is the first step and activation of responses with the C terminus (message) is the second step.